Motor Learning Development among Physical Education Students: Instructional Implications - Bachtiar Bachtiar; M.Risky Adi Wijaya; Agung Widodo; Sufitriono; Nahid Ayad (Attractive : Innovative Education Journal, 2026)
Motor skill learning is a fundamental aspect of physical education, particularly in preparing students of Physical Education, Health, and Recreation (PJOK) to become professional educators. However, its implementation in higher education continues to face challenges, ranging from the dominance of mechanistic instructional approaches to the limited integration of theory and practice in the post–COVID-19 pandemic period. This study aims to examine the development of motor learning among PJOK students and to formulate its implications for instructional practice in higher education. This study employed a systematic literature review with content analysis of 30 published articles from the period 2015–2025, retrieved from Scopus, Web of Science (WoS), Google Scholar, DOAJ, ResearchGate, and Garuda databases. The findings indicate that motor learning is influenced by individual factors, learning environments, instructional strategies, and educational policies. Innovations in digital media (e.g., Lectora and multimedia flipbooks), blended-gamified approaches, and the integration of theory and practice have been shown to effectively enhance students’ motivation, conceptual understanding, and motor skills. This review concludes that motor learning in higher education requires a paradigm shift toward adaptive, evidence-based strategies aligned with the digital era. Practically, these findings call for lecturers to integrate innovative media, institutions to provide adequate infrastructural support, and students to develop pedagogical readiness and character as future PJOK teachers.